Hjulgraven fra Storehøj ved Tobøl i Ribe Amt - Thrane, Henrik (Kuml, 1962)
The Wheel-grave from Storehøj, near Tobøl, Ribe County In 1950, during the unskilled excavation of a barrow in Tobøl, Føvling Parish, Ribe County, a board was discovered, lying north-south, on which a miniature wheel was found, together with the remains of daggers, 6 buttons, 3 amber beads and 1 gold spiral ring (fig. 3). This grave, which lay at the edge of the mound, was presumably an oak-coffin grave. The centre of the mound was excavated in 1893 by the National Museum (fig. 2). In 1961 the Antiquarian Collection in Ribe made a further examination 1) and found a completely destroyed grave with only a corner undisturbed (figs. 4-5). Pieces of oak (coffin) 4) were found in disturbed soil together with a number of bronze fragments, 5 amber beads, 1 jet head, 1 bronze button, potsherds and fragments from the objects found in 1950. As the finders maintain that they covered the board again after having swept it clean, others must have visited the site subsequently and broken the board. Holes in the bottom of the grave were presumably left by stones used to support the coffin. The objects discovered are: Gold spiral ring of double wire, 0.12 cm. thick, weight 18.3 gr., purity 875 ‰ (fig. 6), (found 1950) 6). 8 amber beads with cylindrical perforation (figs. 7-8); 2 are barrel-shaped, 2.1-1.0 cm. long, (1961); 5 more disc-shaped, 1.6-1.1. cm. in diameter, (1950 & 1961); 1 a 6-sided, facetted head, 2.3 cm. long, (1950). 1 jet bead 7), 7-sided, facetted, with cylindrical perforation (figs. 7 & 8,5), 4.2-7 cm. long, (1961). Dagger-blade fragment of bronze with lozenge-shaped section (figs. 7 & 9,2), 3.3 cm. long, (1950); blade fragment (figs. 7 & 9,3), with lozenge-shaped section and recessed edge, 6.2 cm. long, (1950); blade fragment with midrib (figs. 7 & 9,1), 13.3 cm. long, (1961). Pommel with openwork elliptical plate with concentric circles (figs. 9 & 10), having 2 horizontal rivets above and 2 in the socket, 5.2 X 4.2 cm., (1950 & 1961). Fragments of thin wooden plates from a sheath (fig. 9,4) 9) 47a). Disc-shaped pin-head with raised rim, providing room for an inlay disc on the top and with horizontal lines at the base of the head (figs. 8,21 & 10), diameter 1.8 cm., (1961), and a fragment of a pin-point, (1961) (fig. 8,24). 2 pieces of a twisted bar (fig. 8,19), (1961). 1 bar, square in section, with 4 branches at one end (figs. 7 & 8,1), 5.4 cm. long, (the bar 1950 together with the wheel, the forked part 1961). Fragment of round bronze disk with two round perforations (fig. 8,27), (1961), together with various unidentifiable fragments, (1961). 5 conical buttons with oblique edge and flat inside cross-bar (figs. 8,14-18 & 10, diameter 1.9-2.3 cm., (1950). 2 conical buttons with flattened top, grooved base and flat inside cross-bar (figs. 8,12-13 & 10), diameter 2.1-2.3 cm., (1950 & 1961). Piece of red hæmatite with polished sides (figs. 7 & 8,6), (1961)8). Potsherds with cylindrical neck and horizontal moulding at the junction of the neck and body (fig. 15). Coarse ware, horizontally smoothed, with an even outer surface. Height c. 11 cm., rim diameter 11 cm., (1961). Fragments of a bronze wheel (figs. 11-14), with broad cylindrical hub, angular spokes and broad rim with a sharp tread. Along the edges of the spokes is a band of strokes delimited by a single line. One side of the rim (figs. 11 & 13) is ornamented with two double lines, between which, on either side of the spokes, are 2 opposed obliquely hatched triangles, and at the spokes a group of curves. Outside the distal double line is a row of oblique strokes. On the other side (figs. 12 & 14) there are also double lines and a triple curve opposite the spokes, and inside the distal double line, a row of oblique strokes. Diameter 17.7 cm., internal hub diameter 2.3 cm., (1950, small piece 1961). Fig. 8,20 possibly belongs to the wheel (1961). Whilst the grave must be an acentral oak-coffin grave of the type known from the Middle Bronze Age (Ældre Bronzealder) 10), the central grave (fig. 16), is more likely a plank coffin with a stone setting. It contained nothing, but the type is probably Middle Bronze Age 11). The mound proved to be built of turves and contained a hard pan like other barrows with well preserved oak coffins. Gold spiral rings, as in fig. 6, occur in several instances as ear-rings 13) and that interpretation must be valid here also. The type cannot be dated exactly within periods II-III. Oval amber beads (figs. 7 & 8,1-11), are found in the Middle Bronze Age graves in Denmark 14-17) and down to South Germany 18) and similar beads occur as early as the Neolithic period 19). The same form is found in glass 20). Barrel-shaped amber beads (figs. 7 & 8,2-3), are known from Middle Bronze Age graves in Denmark 21-22) and North Germany 23). The facetted type is recorded only once from Denmark 26) and once from Germany 26) and presumably imitates jet beads as figs. 7 & 8,527). Amber beads are not frequent in the Middle Bronze Age 29); just as in the late Jutland battleaxe culture 28) only 1-2 are found in each grave. The finds attest their use as necklaces and bracelets 30). The Jack of amber in Scandinavian finds is attributed to export to the south 32). The jet head (figs. 7 & 8,5) is the first from Scandinavia and presumably imported from the British Isles, although exact parallels are not known 37). A head from Lüneburg having a different shape 35), seems to be the only other jet head from the Middle Bronze Age in Northern Europe. Jet occurs in Great Britain, France, Spain and Germany 33, 36). The blade fragments (figs. 7 & 9) seem to derive from perhaps only two daggers. The blade types are well known in Denmark in period II 38-41). The pommel (figs. 9 & 10), is also a well known type in period IIbc among the indigenous forms 44-46). The pin (figs. 8,21 & 10) is like the so-called "Zargenkopfnadel", known from Silesia and Poznan and in a few specimens from Brandenburg and Pomerania 48). It seems to be typologically early and must be dated to period II. It may better be compared to pins from the German Tumulus culture of Br. C 48a). Another Silesian pin-type was found in a barrow near Ravnsby, Lolland, in an oak coffin (fig. 17) 49), but was more likely imported from Pomerania 50), testifying to the same eastern connections as the Tobøl pin. The fork (figs. 7 & 8,1) Jacks parallels, but has perhaps something to do with the wheel. A series of fragments cannot be assigned to any definite type. The buttons (figs. 8 & 10) belong to a group ascribed to period II 52) but have certain peculiarities and similarities to some German buttons 53). In women's graves, 3-5 and sometimes as many as 10 specimens are found, but normally larger than the Tobøl examples 55). They are worn on the skirt or belt 57). In men's graves there are normally 1-3, and there they are considered to have been cloak fasteners 54-56). The lump of hæmatite (fig. 8,6) is polished and has presumably been used to grind colour from for make-up 59, 61 ). A comparable piece is known from a contemporary grave in Schleswig 60). The pot (fig. 15) differs from other Middle Bronze Age pottery in the encircling moulding, which recalls contemporary north-west German pottery 62). The vessel may indicate influence from this region, but otherwise corresponds in thickness and surface treatment to the ordinary contemporary Danish ware. Miniature wheels are known from model carts, first and foremost the sun-chariot from Trundholm, whose original 6 wheels are smaller and slimmer than the Tobøl wheel (fig. 18) 63). A non-surviving sun-chariot is recorded from Scania 64-65). The wheeled cauldrons from Skallerup 51), Ystad 66) (fig. 19), Peckatel 67) and Milavec 68) are celebrated, other wheeled vehicles largely unpublished 69). Wheeled cauldrons seem to presuppose the existence of 4-wheeled vehicles, whilst the construction of the Trundholm chariot is determined by its purpose. The "Deichselwagen" from Silesia are more recent, but have the same type of wheel 70-71a) (fig. 20). Stray finds are known in earthenware and bronze, some in miniature 71), some in life size 72), from Early and Late Bronze Age over a large part of Europe. In the Orient, the spread of the horse and the two-wheeled war-chariot can be followed with the help of literary sources and pictorial representations from Hammurabi onwards 73) and a complete chariot is preserved from Thebes in Egypt 74). From Asia Minor they spread most likely to Greece, where the stelae from the shaft graves at Mycenae (fig. 21) 75-76) first testify to the presence of the chariot, and later paintings etc. emphasize it importance. The shaft-grave scenes differ markedly from the Egyptian and those from Asia Minor, in that the driver does not use the bow, but carries a sword or lance. The next station is the Val Camonica rock engravings 77), which Anati connects with Mycenae 78); a connection is also drawn between miniature wheels from South-east Europe and Mycenean influence. In Southern Scandinavia also, the war-chariot occurs on rock engravings 80) (fig. 22). The most celebrated is the Kivik grave 81), the date of which is uncertain, but which is almost certainly later than the Trundholm chariot 82). The latter, together with the contemporary Tobøl wheel, constitutes the earliest evidence of wheeled transport in Northern Europe. Since the 4-spoked wheel appears to spread in company with the chariot, these two finds must evidence knowledge of war-chariots in Scandinavia in period II. The wheels are "sophisticated" and cannot be the first fumbling attempts at making 4-spoked wheels. The preceding development can hardly have taken place in Scandinavia, but in central Europe, where more primitive 4-spoked wheels are known 71, 79). Behind the dispersal -from Central to Northern Europe in Br. D-period IIbc -III -the Mycenean culture seems to be discernible, but with a considerable retardation in Central Europe. Observations of wheel-marks under a barrow in Arnitlund, from the Middle Bronze Age 84), seems to support the Trundholm and Tobøl evidence of wheeled transport, but the interpretation is still uncertain. The Tobøl wheel differs from all other bronze wheels, in being decorated on both sides. It may be that is was designed to be used alone. The very large hub diameter points to a wooden axle. Perhaps one should picture the wheel in a kind of fork 85-86). The wheel is also a symbol of the restless sun and is known in this connection from rock engravings. Presumably this idea lies behind the Tobøl deposition 87). Other sun symbols found in graves are the familiar sun discs of gold 89-91) and the helt plates. The somewhat later gold vessels belong to the same cycle 92). The plaited band ornament of the wheel is known in period II in Denmark 93), but its origin is uncertain. It is also known from the Early Bronze Age in Switzerland and Ireland 94) ; otherwise first in period III 95). Multiple curves are rare in the Danish Middle Bronze Age 96), more usual in the Late 97). Lines flanked with oblique strokes are also known from the Middle Bronze Age in Denmark 98). On the other hand, the rhythmical placing which emphasises the quartering of the wheel is otherwise unknown. Normally, an unbroken continuous ornament is the rule. The ornamentation can be dated to period II, but it is not quite clear whether it is indigenous or foreign. All the datable artefacts from the grave, which despite its mode of discovery should be regarded as an integral find, belong together in period II. As the find lies in zone II, it cannot be dated more accurately than to IIbc 99). The artefacts would seem to indicate the burial of a woman 101-102), but no bones were found. In period II there was a growth of prosperity in south-west Jutland which must be seen against the background of the trade route along the west coast of Jutland from the mouth of the Elbe to the Limfjord 103). Along the Kongeå between Tobøl and Plougstrup is a group of 26 barrows, (fig. 23) several of which have yielded Middle Bronze Age finds, among them several gold spiral rings as in fig. 6. Sophus Müller believed that a route from Esbjerg-Hjerting crossed the Kongeå at Villebøl near Tobøl on its way to Gram and farther south 104). The Tobøl grave shows the extensive trading contacts with North-west Germany, England and the Baltic area. The last two areas are otherwise only sparsely represented in Denmark in period II and these connections stress the importance of the grave. It is one of the richest and most unusual graves known from the Middle Bronze Age in Scandinavia. Henrik Thrane.